Umedalen Skulptur 98. - Sörlin, Sverker; Galleri Stefan Andersson, Umea (Umea : Umedalens skulpturpark, 1998)
Baechler, Donald ; Cemin, Saint Clair ; Balka, Miroslaw ; Ekström, Johanna ; Gianakos, Cristos ; Isaeus-Berlin, Meta ; Gormley, Antony ; Wisniewski, Jeffrey ; Not Vital ; Horn, Roni ; Bourgeois, Louise ; Bergström, Bigert & ; Kapoor, Anish ; Johansson, Peter ; Hake, Claes ; Wolgers, Dan ; Kirschenbaum, Bernard ; Kleen, Lars ; Rheinsberg, Raffael ; Englund, Lars ; Kjellgren, Jonas ; Löfdahl, Eva ; Naraha, Takashi ; Nonas, Richard ; Persson, Roland ; Schwartz, Buky ; Aberg, Mikael ; Gunnars, Carina
biografie
Umedalen Skulptur 98, Umedalens skulpturpark, Umea, 7.6. - 13.9.1998
Engels & Zweeds
kunstcatalogus